Pengalaman Perawat Dalam Dokumentasi Asuhan Keperawatan Berkualitas - Ridal Sagala; Nancy Rehata; Karina Sekar Galuh; Josep Ruskandi; Jennifer Simaremare (Malahayati Nursing Journal, 2025)
ABSTRACT Nursing care documentation is a record that contains all information about the client needed to determine the diagnosis, prepare plans, implement, evaluate systematically and confidentially. Nursing care documentation is written evidence of nursing care provided by nurses to clients, and is a reflection of quality nursing care. To explore in depth the experience of nurses in quality nursing care documentation in Bougenville Unit 1, Advent Hospital Bandung. A qualitative descriptive phenomenology study was conducted that recruited 6 respondents within purposive sampling. Data collection in-depth interviews used face to face, and data analysis using the Colaizzi’s method. There are 6 themes that emerged in this study, including 1) Time constraints, 2) Internet network system, 3). Increasing knowledge and skills, 4) Electro Medical Record (EMR) documentation, 5) Workload, and 6) Manpower requirements. Good nursing care documentation can occur if there is good time management, a well-running technology system, a good level of knowledge and skills, a high level of knowledge and skills, minimal workload, and the need for personnel in the unit according to the level of patient needs. Keywords: Documentation, Quality Nurisng care, Nurses.  ABSTRAK Dokumentasi asuhan keperawatan adalah catatan yang memuat seluruh informasi tentang klien yang dibutuhkan untuk menentukan diagnosis, menyusun rencana, implementasi, evaluasi secara sistematis dan rahasia. Dokumentasi asuhan keperawatan merupakan bukti asuhan keperawatan secara tertulis yang diberikan perawat kepada klien, dan merupakan cermin dari asuhan keperawatan berkualitas. Untuk menggali secara mendalam tentang pengalaman perawat dalam dokumentasi asuhan keperawatan berkualitas. Menggunakan metode kualitatif fenomenologi deskriptif dengan 6 responden perawat yang diambil dengan purposive sampling. Pengumpulan data dengan in depth interview face to face dan analisa data menggunakan metode Colaizzi. Tema yang muncul dalam penelitian ini sebanyak 6 diantaranya adalah 1) Keterbatasan waktu, 2) Sistem jaringan internet, 3). Peningkatan pengetahuan dan keterampilan,  4) Dokumentasi Elektro Medical Record (EMR), 5) Beban kerja, serta 6) Kebutuhan tenaga. Dokumentasi asuhan keperawatan yang baik bisa terjadi jika manajemen waktu yang efektif, sistem teknologi berjalan lancar, peningkatan pengetahuan dan keterampilan yang baik, beban kerja dan kebutuhan tenaga dalam satu unit disesuaikan dengan tingkat kebutuhan pasien. Kata Kunci: Dokumentasi, Asuhan Keperawatan Berkualitas, Perawat